The pale of settlement : stories - Singer, Margot (Flannery O'Connor Award for Short Fiction., 2007)
In settings from Jerusalem to Manhattan, from the archaeological ruins of the Galilee to Kathmandu, The Pale of Settlement gives us characters who struggle to piece together the history and myths of their familys past.